FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MELAKUKAN ALIH FUNGSI LAHAN PERTANIAN KE LAHAN NON PERTANIAN DI KECAMATAN KURANJI DAN KECAMATAN KOTO TANGAH KOTA PADANG (Universitas PGRI Sumatera Barat, 2012)
ABSTRACTThis study examines the decision of farmers to convert agricultural landinto non-agricultural land in Padang city. It is associated with widespread use ofagricultural land which has now changed its function into non-agricultural landuse due to construction progress. The study was conducted in Kuranji District andKoto Tangah District in Padang city.The research method used in this study is a quantitative research method,namely to determine the factors associated with the decision of farmers to convertagricultural land into non-agricultural land. The sample in this study were drawnfor the non-random sampling. Respondents were people who were directlyinvolved with the utilization of space in the area of agricultural households inparticular.